2017
DOI: 10.1121/1.5001903
|View full text |Cite
|
Sign up to set email alerts
|

Localization performance correlates with binaural fusion for interaurally mismatched vocoded speech

Abstract: Bilateral cochlear implant users often have difficulty fusing sounds from the two ears into a single percept. However, measuring fusion can be difficult, particularly with cochlear implant users who may have no reference for a fully fused percept. As a first step to address this, this study examined how localization performance of normal hearing subjects relates to binaural fusion. The stimuli were vocoded speech tokens with various interaural mismatches. The results reveal that the percentage of stimuli perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Another factor that may contribute to the early and consistent benefit observed for CI recipients in the present study is the relatively deep insertion of the MED-EL standard electrode array. Monaural speech perception and binaural processing can be degraded by a shift in the mapping of place to frequency ( Suneel et al., 2017 ; Svirsky, Talavage, Sinha, Neuburger, & Azadpour, 2015 ; Wess et al., 2017 ). For example, studies of dichotic vocoded speech recognition with normal-hearing listeners suggest that performance is detrimentally affected by a mismatch in place to frequency mapping across ears ( Wess et al., 2017 ; Zhou, Li, Yuan, Galvin, & Fu, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor that may contribute to the early and consistent benefit observed for CI recipients in the present study is the relatively deep insertion of the MED-EL standard electrode array. Monaural speech perception and binaural processing can be degraded by a shift in the mapping of place to frequency ( Suneel et al., 2017 ; Svirsky, Talavage, Sinha, Neuburger, & Azadpour, 2015 ; Wess et al., 2017 ). For example, studies of dichotic vocoded speech recognition with normal-hearing listeners suggest that performance is detrimentally affected by a mismatch in place to frequency mapping across ears ( Wess et al., 2017 ; Zhou, Li, Yuan, Galvin, & Fu, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been argued that binaural hearing in patients with a unilateral CI and contralateral acoustic hearing is limited by the asymmetry between ears, particularly with respect to the mapping of frequency to place of excitation in the cochlea ( Wess, Brungart, & Bernstein, 2017 ). These asymmetries could interfere with binaural fusion, which is thought to be a prerequisite for the optimal use of binaural spatial cues ( Kan, Stoelb, Litovsky, & Goupell, 2013 ; Ma, Morris, & Kitterick, 2016 ; Suneel, Staisloff, Shayman, Stelmach, & Aronoff, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…While rarely a problem in acoustic hearing, the cochlear place of electrical stimulation is determined by physical electrode location. Thus, many BI-CI and most SSD-CI users have frequencymismatched ears (Kawano et al, 1998;Aschendorff et al, 2005;Landsberger et al, 2015), which can reduce binaural benefit for speech understanding (Wess et al, 2017;Sagi et al, 2020) and localization (Suneel et al, 2017). In normal-hearing systems, SOC neurons are tuned to respond to binaural inputs from matched cochlear places.…”
Section: Introductionmentioning
confidence: 99%
“…NH listeners show reduced ILD sensitivity for frequency-mismatched uncorrelated noise bands ( Francart & Wouters, 2007 ) and acoustic pulse trains ( Goupell, Stoelb, Kan, & Litovsky, 2013 ). Vocoder simulations of SSD-CI listening have shown that interaural place mismatch can reduce subjectively reported binaural fusion ( Aronoff, Shayman, Prasad, Suneel, & Stelmach, 2015 ; Suneel, Staisloff, Shayman, Stelmach, & Aronoff, 2017 ), the binaural integration of speech information ( Ma, Morris, & Kitterick, 2016 ), and the ability to perceptually separate concurrent speech ( Wess et al., 2017 ). These results suggest that SSD-CI listeners might benefit if the CI frequency-allocation table (FAT) were adjusted to deliver each acoustic frequency to the electrode that is stimulating the spiral ganglia corresponding to the basilar membrane location that is naturally tuned to that frequency.…”
Section: Introductionmentioning
confidence: 99%